2017
DOI: 10.3390/toxins9040120
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Fusarium Head Blight Complex of Malting Barley in a Three-Year Field Experiment in Italy

Abstract: In this study, conducted for three years on eleven malting barley varieties cultivated in central Italy, the incidence of different mycotoxigenic fungal genera, the identification of the Fusarium species associated with the Fusarium Head Blight (FHB) complex, and kernels contamination with deoxynivalenol (DON) and T-2 mycotoxins were determined. The influence of climatic conditions on Fusarium infections and FHB complex composition was also investigated. Fusarium species were always present in the three years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
34
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 68 publications
7
34
1
Order By: Relevance
“…However, in Umbria, F. avenaceum was present at similar levels as of F. graminearum. This is a further confirmation of what previously observed in the Umbria region over the last few years, where F. poae and F. avenaceum seemed to interchange as the dominant members of the Fusarium community associated with durum wheat and malting barley, while, F. graminearum showed a constant incidence, never acting as the main species of the complex [7,[72][73][74]. Interestingly, particularly based on DFB isolations, F. proliferatum showed a high incidence in the FHB complex of durum wheat grains harvested in all investigated regions.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, in Umbria, F. avenaceum was present at similar levels as of F. graminearum. This is a further confirmation of what previously observed in the Umbria region over the last few years, where F. poae and F. avenaceum seemed to interchange as the dominant members of the Fusarium community associated with durum wheat and malting barley, while, F. graminearum showed a constant incidence, never acting as the main species of the complex [7,[72][73][74]. Interestingly, particularly based on DFB isolations, F. proliferatum showed a high incidence in the FHB complex of durum wheat grains harvested in all investigated regions.…”
Section: Discussionsupporting
confidence: 90%
“…Surprisingly, despite the significant F. proliferatum presence, very low fumonisin levels (compared to those recovered in maize by Covarelli et al [79]) were detected (a very low percentage of samples only in Emilia Romagna). Low levels of fumonisin contamination on wheat infected with F. proliferatum were also recorded in other wheat-cultivation areas [74,80].…”
Section: Discussionmentioning
confidence: 72%
“…In Europe, cereal grains are frequently contaminated by Fusarium species such as F. culmorum , F. avenaceum , and F. poae ; however, generally, the most common contaminant is F. graminearum [ 7 ]. The occurrence of Fusarium species, however, is subject to climatic changes over a period of years and to agricultural practices, such as pesticide applications and nitrogen fertilization [ 8 , 9 , 10 ]. In Sweden, F. avenaceum was the species with highest incidence on wheat kernels, followed by F. poae , whereas F. graminearum was the most abundant [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the Umbria region, in central Italy, Beccari et al [ 11 ] found that the predominant Fusarium species on malting-barley grains was F. avenaceum , followed by F. graminearum and F. poae . In a three-year field study, F. avenaceum (in 2012) and F. poae (in 2013)—but never F. graminearum —were the most frequently isolated species from barley grains [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies frequently detected DON in barley grains, malt and also beer (Schwarz 2017). In particular, the presence of DON in malting barley samples in Europe, including Italy, seems to be stable over the years and generally below legal limits (Berguete 2012, Beccari et al 2016, Beccari et al 2017. During beer production process, DON seems to be reduced with respect to the raw material, but its levels may increase during malting, in particular during the germination phase (Schwarz 2017).…”
Section: Manuscript Received December 2017mentioning
confidence: 99%